A study of lighting techniques and an automatic vision system - Prahladan Ganesan. (2010)
More and more manufacturing companies are using machine vision technology to improve their productivity and reduce costs. At the core of this growth in machine vision are manufacturer’s ever-increasing demands over the quality of manufactured parts. Therefore in a machine vision system, the image processing and illumination techniques is the key to successful inspection. The quality of the image depends on various important factors such as illumination techniques, camera, lens, defect characteristics. This report discusses about some of these factors using the actual data from the industry.